Drought, psychosocial stress, and ecogeographical patterning: Tibial growth and body shape in Samburu (Kenyan) pastoralist children. Issue 4 (30th April 2022) - Straight, Bilinda; Hilton, Charles E.; Naugle, Amy; Olungah, Charles Owuor; Ngo, Duy; Qiao, Xi; Needham, Belinda L.
Abstract: Objectives: This study of Samburu pastoralists (Kenya) employs a same‐sex sibling design to test the hypothesis that exposure in utero to severe drought and maternal psychosocial stress negatively influence children's growth and adiposity. As a comparison, we also hypothesized that regional climate contrasts would influence children's growth and adiposity based on ecogeographical patterning. Materials and Methods: Anthropometric measurements were taken on Samburu children ages 1.8–9.6 years exposed to severe drought in utero and younger same‐sex siblings (drought‐exposed, n  = 104; unexposed, n  = 109) in two regions (highland, n  = 128; lowland, n  = 85). Mothers were interviewed to assess lifetime and pregnancy‐timed stress. Results: Drought exposure associated to lower weight‐for‐age and higher adiposity. Drought did not associate to tibial growth on its own but the interaction between drought and region negatively associated to tibial growth in girls. In addition, drought exposure and historically low rainfall associated to tibial growth in sensitivity models. A hotter climate positively associated to adiposity and tibial growth. Culturally specific stressors (being forced to work too hard, being denied food by male kin) associated to stature and tibial growth for age. Significant covariates for child outcomes included lifetime reported trauma, wife status, and livestock. Discussion: Children exposed in utero to severe drought, a hotter climate, and psychosocial stress exhibited growth differences in our study. Our results demonstrate that climate change may deepen adverse health outcomes in populations already psychosocially and nutritionally stressed. Our results also highlight the value of ethnography to identifying meaningful stressors. Abstract : Samburu woman in lowland homestead.